Hirayama Disease (monomelic amyotrophy) - Alkan, Gökhan; Akgöl, Gürkan; Gülkesen, Arif; Kaya, Arzu (My University, 2017)
Hirayama disease (HD) or monomelic amyotrophy (MA) is a rare muscular atrophy that affects young Asian males, usually occurs in one of the upper limbs that progresses slowly. It is diagnosed by means of electromyographic/electroneurographic conduction speed studies and by magnetic resonance imaging (MRI) of the spinal cord. In this paper two different HD case is reported
Keywords: Genel ve Dahili Tıp; Nörolojik Bilimler